Is the Appropriateness of Emotions Culture-Dependent? The Relevance of Social Meaning - Anna Welpinghus (Journal of Social Ontology, 2018)
This paper contributes to the question to what extent the socio-cultural context is relevant for the appropriateness of emotions, while appropriateness of an emotion means that the emotion entails a correct, or adequate, evaluation of its object. In a first step, two adequacy conditions for theories of emotions are developed: the first condition ensures that the socio-cultural context is not neglected: theories must allow for the fact that appropriateness often depends on the social meaning of the emotion’s particular object. The second condition rules out implausible forms of cultural determinism. In a second step, an account that meets both conditions is presented: the Acceptance within Social Context account.